A cross-fostering experiment reveals that prenatal environment affects begging behaviour in a cooperative breeder. (April 2015) - Paquet, Matthieu; Covas, Rita; Doutrelant, Claire
Abstract : Prenatal breeding conditions have broad influences on maternal allocation to reproduction which can strongly affect future begging behaviours of offspring. The social environment is part of the prenatal environment; however, its influence on maternal allocation has been poorly investigated and experimental tests linking prenatal conditions to begging behaviour have seldom been conducted. In cooperative breeders the presence of additional carers, the helpers, generally predicts an increase in provisioning during the nestling stage. Since begging is costly, in these species producing offspring that beg less in the presence of helpers may be a way of saving energy not only for the offspring but also for the future survival and reproduction of females. To date, whether mothers may manipulate begging behaviour in relation to helper presence is unstudied. We conducted a cross-fostering experiment in a cooperatively breeding bird, the sociable weaver, Philetairus socius, to disentangle the possible effects of prenatal and postnatal environments on begging behaviour. Pre- and postnatal environments correspond here to the number of carers in the nest of origin and the foster nest, respectively. As predicted, begging was influenced by the prenatal environment, with nestlings originally from larger groups begging less. In addition, chicks fed by more foster birds also begged at a lower rate. We conclude that the prenatal environment influences begging behaviour. This result has important implications for understanding cooperative breeding strategies since producing offspring that beg less with more helpers may allow energy savings for females and related offspring and helpers. Highlights: We cross-fostered clutches to investigate prenatal effect of helpers on begging. We found a negative prenatal effect of helpers' number on early chicks' begging. Chicks fed by more birds begged at a lower rate both early and late after hatching. This result has strong implications for our understanding of cooperatively breeding.